CHITOSAN MUCOADHESIVE BUCCAL FILMS: EFFECT OF DIFFERENT CASTING SOLVENTS ON THEIR PHYSICOCHEMICAL PROPERTIES - Abouhussein, Dalia M. N.; El-bary, Ahmed Abd; Shalaby, Samia H.; El-Nabarawi, Mohamed A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of this work is to investigate the influence of different casting solvents on the physicochemical properties of cetylpyridinium chloride (CPC) chitosan mucoadhesive buccal films. Methods: Screening formulations were prepared by casting solvent technique using organic acids; 1% acetic acid (AA), 1% lactic acid (LA) and inorganic acid; 0.1N HCl (FS1-FS3). Then, 21X31 factorial design study was done using 2 factors; solvent type (AA, LA, Mixture of 0.1N HCl and LA) and solvent concentration (AA and LA; 1%, 2% and mixture of 0.1N HCl: 1% LA; 2:1, 1:2). Films were evaluated for their physicochemical properties through, mechanical properties, mucoadhesion, in vitro release of CPC and antimicrobial activity. Results: The studied factors showed a significant effect on both mucoadhesion and tensile strength. Film casted from 0.1 N HCl was brittle and did not show any elasticity, so it was used in further studies mixed with LA to improve physicochemical properties of the prepared films. Films casted from LA showed swelling for an initial period of 15 min then no more swelling occurred while swelling of those casted from AA occurred throughout approximately 2 h. A film containing 2:1 HCl: LA (F5) dissolved in both media while 1:2 HCl: LA (F6) showed swelling properties. This was reflected on the in vitro release of CPC in which F5 gave higher % released (DE300 min 54.37%) than the other formulations. Conclusion: Casting solvent was proved to have a significant effect on the physicochemical properties of chitosan CPC mucoadhesive films.